Comparative analysis of characteristics and outcomes in hospitalized COVID-19 patients infected with different SARS-CoV-2 variants between January 2020 and April 2022 - A retrospective single-center cohort study - Thomas Theo Brehm; Andreas Heyer; Marcel S. Woo; Marlene Fischer; Marc van der Meirschen; Dominic Wichmann; Dominik Jarczak; Kevin Roedl; Stefan Schmiedel; Marylyn M. Addo; Marc Lütgehetmann; Martin Christner; et al. (Elsevier, 2023)
Background: Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, the roll-out of vaccines and therapeutic agents, as well as the emergence of novel SARS-CoV-2 variants, have shown significant effects on disease severity. Methods: Patients hospitalized at our center between January 2020 and April 2022 were attributed to subgroups depending on which SARS-CoV-2 variant was predominantly circulating in Germany: (i) Wild-type: January 1, 2020, to March 7, 2021, (ii) Alpha variant: August 3, 2021, to June 27, 2021, (iii) Delta variant: June 28, 2021, to December 26, 2021, and (iv) Omicron variant: December 27, 2021, to April 30, 2022. Results: Between January 2020 and April 2022, 1500 patients with SARS-CoV-2 infections were admitted to the University Medical Center Hamburg-Eppendorf. The rate of patients who were admitted to the intensive care unit (ICU) decreased from 31.2% (n = 223) in the wild-type group, 28.5% (n = 72) in the Alpha variant group, 18.8% (n = 67) in the Delta variant group, and 13.4% (n = 135) in the Omicron variant group. Also, in-hospital mortality decreased from 20.6% (n = 111) in the wild-type group, 17.5% (n = 30) in the Alpha variant group, 16.8% (n = 33) in the Delta variant group, and 6.6% (n = 39) in the Omicron variant group. The median duration of hospitalization was similar in all subgroups and ranged between 11 and 15 days throughout the pandemic. Conclusions: In-hospital mortality and rate of ICU admission among hospitalized COVID-19 patients steadily decreased throughout the pandemic. However, the practically unchanged duration of hospitalization demonstrates the persistent burden of COVID-19 on the healthcare system.